Trade openness and FDI inflows in Turkey - (:unkn) unknown (Asociacion Euro-Americana de Estudios del Desarrollo, 2015)
Turkey's politics after the decisions on January 24, 1980, have been a milestone in terms of the opening up of the economy. This external trade openness process of Turkey has also attracted multinational companies and has led to further important steps in foreign direct investments (FDI). In this study, we aim to examine the relationship between FDI and openness over the period 1986-2010. We examine not only the relationships between the two variables, but also the impact of leading macroeconomic variables on the FDI. Openness is also used among the variables to explain FDI and the impact of openness on the FDI in the estimated model has been determined. Granger causality analysis has been performed to determine the relationship between the variables in the model and it is concluded that the cause of FDI is trade openness. On the other hand, the effect of openness in the framework of Turkey's economy created with the model obtained, the findings are discussed along with other variables.
Keywords: Foreign direct investments; Granger causality test; Openness; Unit root tests